Intergenerational Integration in Community Building to Improve the Mental Health of Residents—A Case Study of Public Space - Jianbin Wu; Kin Wai Michael Siu; Linghao Zhang (Behavioral Sciences, 2023)
This study defined intergenerational integration in communities at a theoretical level and verified whether a series of measures could facilitate negotiation and communication between community residents and other stakeholders to generate a positive and healthy community environment and gradually improve intergroup relations. Specifically, we applied community psychology and used Hongqiao New Village in Shanghai, China, as a research site to explore intergenerational conflict in public community spaces. The research was divided into two stages: an input stage and an output stage. In the input stage, participatory research and tea parties were used to deeply explore residents’ public space requirements. In the output stage, we tested the validity of the theory by using the Intergenerational Attitude Scale to investigate whether the intergenerational relationships were changed by the co-creation intervention. The results showed that the intervention caused a decrease in the incidence of conflict between residents using the square and caused some children to join the older groups in their activities. We thus propose a theoretical system model of intergenerational integration strategies that incorporates elements of integration, disagreement, and synergy in intergenerational interactions. Overall, this paper provides new ideas for building a community environment that supports mental health and improves intergenerational relationships and social well-being.